A study on ground improvement using a combination of stone and concrete columns - Pudaruth, Yogendra (Department of Civil Engineering, 2019)
Stone column is a cost-effective ground improvement technique that is typically employed for low-rise buildings and road embankments. This technique mainly uses naturally occurring materials as its load transferring medium. However, stone columns have some constraints because of the loose interactions between their aggregates which can lead to uncontrolled settlements, especially in soft soils. As a result, their performance is usually improved by the inclusion of geosynthetics either in layers or as a confinement. However, there was a lack of studies that used a binder within the stone column aggregates with a view to limit the bulging/lateral spreading of its aggregates in such soils. In this study, the upper portion of the stone columns was replaced by different grades of unreinforced concrete. The length of the concrete, as well as the depth of the soil beneath the columns, were varied. The effects of these different variables, when the resulting column was subjected to an applied load, were investigated. The optimum configuration of the above was identified and its resulting change in performance when it was combined with a reinforced bedding layer was studied. Considering application/installation procedures on site, it was best deemed to install and test a geosynthetic-reinforced bedding layer on top of, rather than within, the stone column. It was observed that increasing the grades of concrete did not have any consistent influence on the performance of the resulting columns when there was a considerable layer of soil beneath them. The hybrid stone columns (combination of stone and concrete) performed better than the normal stone column and even to a full concrete column of the same length in several cases. Physical modelling revealed that the bulging length ranges from 2.0-2.4D (D is the diameter of the column). Test results for the optimum hybrid stone column yielded a maximum load improvement factor of 3 to 6 folds (200% to 500% increase in bearing capacity) depending on their respective configuration compared to the unreinforced soil. The improvement factor was further increased to 9.9-fold (nearly 900% increase in bearing capacity) when the optimum hybrid stone column was tested in combination with a reinforced bedding layer. The findings from this research can be used to enhance and promote the stone column ground improvement technique while still providing an economical advantage as well.